Alchornoic acid derivatives from the fruits of Alchornea cordifolia (Schumach. & Thonn.) Muell. Arg. (Euphorbiaceae). (February 2018) - Ebessa, Virginie; Tiani, Gesquiere Laure M.; Tchamgoue, Joseph; Kouam, Simeon F.; Ngadjui, Bonaventure T.; Green, Ivan R.; Choudhary, Muhammad I.; Tane, Pierre
Graphical abstract: Highlights: Two new alchornoic acid derivatives were isolated from Alchornea cordifolia . The structures were elucidated on the basis of chemical and spectroscopic data. The new compound, deepoxyalchornoic acid showed very weak antibacterial activity on the tested strains. Abstract: Two alchornoic acid derivatives, deepoxyalchornoic acid (1 ) and bisalchornoicester (2 ), together with six known compounds, alchornoic acid (3 ), gallic acid, 4- O -methylgallic acid, shikimic acid, kaempferol-3- O -galactoside and 2, 3-dihydroxypropyl octacosanoate were isolated from a dichloromethane/methanol-soluble extract of the ripe fruits of the Cameroonian medicinal plant Alchornea cordifolia . The structures of the new fatty acid derivatives were elucidated by interpretation of their HRESIMS, 1D and 2D NMR spectroscopic data and by comparison with those reported in the literature. Some of the isolated compounds demonstrated inhibition activity against the microbial strains Escherichia coli, Klebsiella pneumoniae and Citrobacter braakii .